Esophageal motor disorders in subjects with incidentally discovered Chagas disease: a study using high-resolution manometry and the Chicago classification - Remes-Troche, J. M.; Torres-Aguilera, M.; Antonio-Cruz, K. A.; Vazquez-Jimenez, G.; De-La-Cruz-Patiño, E. (Diseases of the esophagus, 2014)
Summary In patients with chronic indeterminate Chagas disease, conventional manometry has shown that 25–48% had esophageal motor disorders. Recently, esophageal high‐resolution manometry (HRM) has revolutionized the assessment of esophageal motor function. In this study, we performed esophageal HRM in a group of subjects with incidentally positive serological findings for Trypanosoma cruzi. In this prospective observational study, we evaluated subjects who had positive serological tests for Chagas disease detected during a screening evaluation for blood donation. All subjects underwent symptomatic evaluation and esophageal HRM with a 36 solid‐state catheter. Esophageal abnormalities were classified using the Chicago classification. Forty‐two healthy subjects (38 males) aged 18–61 years (mean age, 40.7 years) were included. When specific symptoms questionnaire was applied, 14 (33%) subjects had esophageal symptoms. Esophageal high‐resolution manometry revealed that 28 (66%) of the subjects had an esophageal motility disorder according to the Chicago classification. Most common findings were hypocontractile disorders in 18 subjects (43%) and esophagogastric junction (EGJ) outflow obstruction in 6 (15%). Esophageal high‐resolution manometry reveals that up to two thirds of the subjects with an incidental diagnosis of Chagas disease have esophageal abnormalities. This technology increases the detection and allows a more complete assessment of esophageal motor function in subjects infected with T. cruzi even in the early stages of the disease.